A Study of Computer Literacy Among Stm Teachers in Colleges of Education in Nigeria - Moses, Timothy; Yakubu, Sani (Universitas Terbuka, 2020)
Information and Communication Technology has changed instructional conveyance. Advancement recorded in information assembling, teaching, and learning collection has given teachers new devices to work with, subsequently the upheaval in the field of training. This study examined computer literacy among Science, Technology, and Mathematics (STM) instructors in Colleges of Education. Discoveries show that the degree of computer proficiency among STM instructors is low. The explanation behind this incorporates few available skillful instructors, insufficient ICT tools in schools, computer phobia, access to Personal Computers (PCs)/PC labs, and absence of ICT devices for STM training. Proposals were anyway made that will help improve the degree of proficiency among STM instructors.